2012
DOI: 10.1542/peds.2012-0095
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-enhancing Behaviors Among Adolescent Girls and Boys

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Emphasis on muscularity has increased in recent decades. Identifying adolescent populations at risk for unhealthy muscle-enhancing behaviors is of considerable importance, yet recent research in the United States is limited in terms of sample diversity and behaviors of interest. WHAT THIS STUDY ADDS:Muscle-enhancing behaviors were common for both boys and girls, and rates were higher than reported previously. Adolescents in high school, of Asian background, in overweight/obese BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
142
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 27 publications
17
142
1
2
Order By: Relevance
“…The overall gender differences and age trends detected in this study were consistent with previous US epidemiologic data on the prevalence of laxative use and muscle-building product use in adolescent and young adult females and males. 7,9,11,15 The results build on previous research on gender and sexual orientation disparities in laxative and musclebuilding product use by highlighting the unique, independent effect of gender conformity in patterning weight control and muscle-building behaviors in heterosexual and sexual minority adolescents and young adults.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The overall gender differences and age trends detected in this study were consistent with previous US epidemiologic data on the prevalence of laxative use and muscle-building product use in adolescent and young adult females and males. 7,9,11,15 The results build on previous research on gender and sexual orientation disparities in laxative and musclebuilding product use by highlighting the unique, independent effect of gender conformity in patterning weight control and muscle-building behaviors in heterosexual and sexual minority adolescents and young adults.…”
Section: Discussionsupporting
confidence: 72%
“…9,10 Project EAT data indicate that 10.5% of adolescent males and 5.5% of females report using other muscle-building products (eg, creatine, hydroxymethylbutyrate, dehydroepiandrosterone, or growth hormone). 11 Beyond gender differences in laxative and muscle-building product use, emerging epidemiologic data indicate disparities by sexual orientation identity (ie, heterosexual vs sexual minority [gay, lesbian, bisexual, mostly heterosexual]). [11][12][13][14] Sexual minority females, particularly those who identify as bisexual or mostly heterosexual, report higher levels of laxative use than their heterosexual peers, 14,15 a finding that runs counter to the popular misperception that sexual minority females are at lower risk for body dissatisfaction and eating disorders.…”
mentioning
confidence: 99%
“…Terms such as "performance-and image-enhancing substances" and "appearance-and performance-enhancing drugs" emphasize their broader appeal. [10][11][12][13] A Minnesota study evaluating various muscle-enhancing behaviors revealed that in an urban high school population, 38.8% of boys and 18.2% of girls reported a history of protein supplement use. 11 The same study revealed rates of use in middle school for boys and girls as 29.7% and 24.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there exists a clear gender difference in the type of weight concerns reported. Compared with girls, boys are more likely to desire an increase in weight gain related to an increase in muscle mass (24) and, indeed, muscle-enhancing behaviours are higher now than in the past among boys (25,26) . Family mealtimes are considered fundamental to the health of adolescents.…”
mentioning
confidence: 99%